Simultaneous azo dye degradation and biohydrogen production by strain L17 form gastrointestinal origin - Hosseinnia, Ali (2014)
Nowadays, with the increase in the population of the world, energy consumption is one of the important issues. Environmental pollution is another issue related to the pollution rise. Hence, simultaneous treatment of the pollution with energy generation is very desirable. Azo dye from textile industry has the potential to be used as feedstock for energy generation, for example hydrogen production via biological treatment. In this study, strain L17 from Enterobacteriaceae family was used to degrade azo dye in microaerophilic condition in different minimal and rich media to select the best media for biohydrogen production via anaerobic fermentation. A minimal medium, MMP5, was chosen as the best media due to the absence of glucose and nutrient broth. L17 was inoculated into the anaerobic MMP5 medium and incubated to detect the hydrogen production, and simultaneous dye degradation. Residual Gas Analyzer was used to detect the production of hydrogen and other gases produced by L17 fermentation. It was found that L17 produced hydrogen as early as 24 hours after fermentation starts. In order to detect potential gene related to this hydrogen production, hydrogen 3 large subunit (hycE) was targeted for PCR amplification, sequencing and amino acids sequence prediction. Hydrogen 3 has been reported to play a role in hydrogen production in Enterobacteriaceae. This study supports the potential for simultaneous azo dye wastewater treatment and hydrogen production using L17 strain as the biological agent.